Islamic Education For Adult New-Muslims (Mualaf) In The Global Era: Malaysian And Indonesian Curricula Comparison - Greentree, Theis; Asmaji Muhtar; Muna Yastuti Madrah (Edukasiana: Journal of Islamic Education, 2025)
This study examines the structure, content, and implementation of Islamic education curricula for adult new-Muslims (Mualaf) in the contemporary global context, utilising a comparative analysis of two established institutions: Hidayah Centre Foundation (HCF) in Malaysia and Mualaf Centre Indonesia (MCI). This research aims to analyse the objectives and components of each curricula, identify their similarities and differences, and evaluate their appropriateness for adult new-Muslims within a multicultural and globalised context. A qualitative multiple case study design was applied, involving data collection through in-person interviews with curriculum developers and educators, together with document analysis. The research uses Bereday’s Comparative Model as a structural framework and employs Transformative Learning Theory and Andragogy principles to analyse the findings. Results indicate that HCF employs a tiered and structured methodology, incorporating individual foundational knowledge (Fard ‘Ayn) alongside community-oriented skills, whereas MCI utilises a more informal and adaptable framework that responds to local contexts. Both programs prioritise practical application and learner transformation; however, they differ in terms of standardisation, assessment, and scalability. The study concludes that both curricula provide valuable educational frameworks; however, improvements in structure and global adaptability could enhance their effectiveness. The findings provide essential insights for the development of globally applicable Islamic education curricula for new-Muslims.